Online Shopping Issues on Consumer Behavior and Their Impact on Repurchase Decisions (A Survey on E-commerce in Indonesia) - Eveline Winfrey; Mulyadi Suhardi; Mohamad Donie Aulia (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2025)
The objectives of this research are 1) to find some important problems of online purchase, 2) to know the effect of problems of online purchase on consumer behavior; 3) to reveal the influence of consumer behavior on repeat purchase decision; 4) to know the effect of problems of online purchase on repeat buying decision through consumer behavior. The present writer employs the research based on the quantitative approach, descriptive and verified design, and survey method. As much as 100 consumers of the major online shops are selected using purposive random sampling as the respondents. The data from the site is analyzed using the partial least square structural equation modeling. The findings of the research are as follows: First, indicators’ effect of the problems of online purchase on consumer behavior falls is moderate. Second, the influence of the behavior of the consumer on the indicators of the buying decision is moderate. Third, the influence of indicators of the behavior of consumer on repeat buying decision ranges from low to moderate effect. Fourth, The effect of the consumer behavior on the indicators of the repeat buying decision is low. Sixth, Problems of online purchase affects Consumer behavior significantly with its indicators. Seventh, Consumer behavior affects significantly the Repeat buying decision. Eight, problems of the online purchase affects the repeat buying decision through the consumer behavior. Keywords: Online Purchase Problems; Consumer Behavior; Repeat Purchase Decision; Quantitative Approach; Partial Least Squares (PLS-SEM)